Integrating Gender in Energy Provision Case Study of Bangladesh - Berthaud, Alexandre; Delescluse, Aude; Deligiorgis, Dina; Kumar, Kabir; Mane, Sunanda; Miyamoto, Satoshi; Ofosu-Amaah, Waafas; Storm, Lara; Yee, Myla (World Bank, Washington, DC, 2014)
Energy sector projects and women's empowerment are crucial to poverty reduction efforts, sustainable development, and achievement of the Millennium Development Goals (MDGs). Energy-related issues are often assumed to be gender neutral. However, energy scarcity can have disproportionately negative effects on women in the developing world. A large proportion of the world's poorest are women, and approximately 70 percent of the energy sources in developing countries come from biomass fuels, which are overwhelmingly the responsibility of women. Historically, this link has not been acknowledged in energy planning and projects, whether governmental or nongovernmental. Similarly, energy as a crucial input to other sectors, such as agriculture, has a myriad of implications when analyzed through a gendered lens with respect to specific times and places. Approaching energy planning in a manner that accounts for changing gender relations can do much to transform the situation of women and their relations to men.